Rapid fabrication and dissolution of pressed 58Ni/Mg matrix targets for 55Co production - Jonathan Siikanen; Stefan Milton; Klas Bratteby; Wilson Lin; Jonathan W. Engle; Emma Jussing; Thuy A. Tran (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Beyond the use of conventional short-lived PET radionuclides, there is a growing interest in tracking larger biomolecules and exploring radiotheranostic applications. One promising option for imaging medium-sized molecules and peptides is ⁵⁵Co (T₁/₂ = 17.5 h, β⁺ = 76%), which enables imaging of new and already established tracers with blood circulation of several hours. Additionally, ⁵⁵Co can be paired with the Auger-Meitner emitter 58mCo (T₁/₂ = 9 h, 100% IC) for radiotheranostic applications. Here we report on 55Co production via the 58Ni(p,α)55Co reaction channel using pressed 58Ni and Mg matrix targets. Results This set up is capable to produce and isolate 240 ± 20 MBq [55Co]Co+ 2 (80% RCY) with 4 ml 0.25 M HEPES at 35 min post End Of Bombardment for 3 h, 25 µA protons irradiation. The RNP of the eluate is 99.98 ± 0.014% as measured 2 h & 17 h post EOB. AMA was determined to 1.5 ± 0.5 GBq/µmol [55Co]Co-DOTA at EOB. Mg dissolves rapidly in the acid mixture, leaving behind a porous, sponge-like Ni matrix increasing the surface area of the Ni and therefore accelerating the dissolution. Conclusion We present a novel, simple, and rapid method to produce ⁵⁵Co with pressed ⁵⁸Ni/Mg matrix targets enabling faster target fabrication and dissolution. By using a simple hydraulic press, mechanically stable target coins useful for solid target irradiation are fabricated within 5 min and can be dissolved in 10 min at room temperature. The foils remain intact after irradiation and can endure irradiation conditions providing sufficient activity (> 200 MBq) for clinical doses. The method presented here using Mg as a support metal for fixation of the actual target material into target coins is applicable for other target combinations as well. Using Mg as a support metal is suitable due to its thermal conductivity, low activation, minimal impact on purification chemistry, softness, ductility, and rapid dissolution in acid.